Hirarc-Based Occupational Safety Risk Analysis in Sprinkler System Installation: Analisis Risiko Keselamatan Kerja Berbasis HIRARC pada Pekerjaan Instalasi Sistem Sprinkler - Rizaldy Fathur Rachman; Kunnati Kunnati; Nilam Puspitasari; Astaman Sultan; Abdul Gamal; Ziko Pratama; Muhammad Raiza (Journal of Public Health Education, 2026)
Introduction: Sprinkler system installation involves manual handling, electrical exposure, hot work, work at height, and interaction with moving equipment, which may result in preventable occupational injuries. Objective: This study aimed to assess occupational safety risks and formulate risk-control measures for sprinkler system installation work at the PT Adiwarna Anugerah Abadi project. Method: A descriptive qualitative study was conducted using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach. Data were collected through workplace observation, questionnaires, and interviews involving 25 supervisors and workers selected by total sampling in December 2025. Risk levels were determined using probability and severity scores and were categorized according to the project risk matrix. Results: The initial assessment identified 26 risks, consisting of 5 low risks, 17 moderate risks, and 4 high risks. High risks included fire during grinding, falls from height, falling objects striking workers, and contact with moving equipment. After implementing engineering, administrative, and personal protective equipment controls, residual risks decreased to 23 low risks and 3 moderate risks. Conclusion: HIRARC provided a structured basis for prioritizing controls in sprinkler installation work. Continuous supervision, compliance with personal protective equipment, permit-to-work implementation, and periodic residual risk review are required to maintain an acceptable level of occupational safety.